FAKTOR – FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTI DAN REAL ESTATE - Yulianson, Willy; Hastuti, Rini Tri (Jurnal Paradigma Akuntansi, 2025)
This study aims to show the influence of firm size, leverage and liquidity partially on firm value. This study uses a sample of company data listed on the Indonesia Stock Exchange (IDX) for 2019-2021. The sampling method used is purposive sampling method and the samples used are 26 companies. the sample used was 78 data which was processed and analyzed using eviews 12 (econometrics views). but it does not have a significant effect, while the firm size variable has a negative relationship to firm value but has a significant effect.